Adverse health outcomes and health concerns among survivors of various childhood cancers: Perspectives from mothers. (7th February 2017) - Hsiao, C.C.; Chiou, S.S.; Hsu, H.‐T.; Lin, P.C.; Liao, Y.M.; Wu, L.‐M.
Abstract : Advanced therapies have improved outcomes and also resulted in a growing risk of long‐term adverse health events. This study intends to estimate incidences of adverse health events and examine differences in adverse health events among childhood cancer survivors, and to understand the concerns of mothers after their child has completed cancer treatment. An explanatory sequential mixed‐method was used. A total of 201 paediatric cancer survivors' mothers with mean age 43.6 years were recruited. Of the survivors, 12.4% experienced five or more adverse health events. The incidence of adverse health events of altered body image, fatigue and neurocognitive problems were 31.54%, 14.77% and 12.53% respectively. Among survivors, significant differences in adverse health events of pain, endocrine problems and altered body image issues were identified. Survivors receiving radiotherapy, bone marrow transplants or completing treatment after 6–10 years experienced significantly more adverse health events. Maintaining health was the greatest concern for mothers, and the qualitative reports of their concerns could be categorised: living in uncertainty, and keeping forward‐looking. Childhood brain tumour survivors were identified as experiencing more adverse health events than other survivors. The need for healthcare teams to consider mothers' health concerns was highlighted.